Din eğitiminde namaz öğretimi - Tuzcu, Kenan (My University, 2012)
İnsan şahsiyetini bütünüyle kapsayan din, inanç, amel ve hizmetler bu hayata yön verir. İbadetler insan hayatının derinliklerini düzenler. İbadetler kişiyi şahsiyetli bir kul yapar. Eğitilmiş bir kulun fiili olan ibadetler, sonuçta yine bir eğitim faaliyeti yapar. Kur'ân verileri ışığında bir değerlendirme yapacak olursak, ibadetlerin, insanın ilgi ve eğilimleriyle ayrılmaz bir birliktelik içerisinde olduğunu görürüz. Namaz insanı kötülükten alıkor, ilgi ve eğilimlerin başıboş, kontrolsüz doyum arayışını engeller. Oruç, özellikle insanın fizyolojik güdülerini hedef alır. Sahib olma ve çıkar güdüsüne zekât ibadeti müdahale ederken, toplumsal ilgi, güven arayışı ve saldırganlık eğilimine hac ibadetiyle yön verilir. Biz bu çalışmamızda İslam Dininin temel ibadetlerinden olan namaz üzerinde bir araştırma yaptık. Namazın önemini, hikmetini ve farziyetini birçok kişi bilmesine rağmen bu ibadeti yapmada bir gevşeklik görülmektedir. Biz de din eğitimcisi olarak namaza karşı olan bu tutumun bir eğitim problemi olduğunu düşünerek konuya yaklaştık. Bu itibarla Kur’an’ın namazı bizlere nasıl öğrettiğini, hangi kelimelerle dikkatimizi çektiğini araştırmaya çalıştık. Hz. Peygamber’in de hem kavli hem de fiili sünnetlerinde namaz eğitimini ashaba nasıl verdiğini çalışmamızda göstermeye çalıştık. Bunun yanında temel kaynaklarımızda bazı İslam alimlerinin de Kur’an ve hadis ışığında namaz hakkındaki görüşlerini tezimize yansıttık. Bu çalışmayla amacımız namaz konusunda doğru bir eğitimdir. Dinin temel şartlarından olan namaz ibadetinin doğru bir eğitimle verilmesi sonucunda hem namaz konusunda devam sağlanacaktır hem de “namazın niteliği” artacaktır. Çalışmamız 4 bölümden oluşmaktadır. Birinci bölümde genel olarak eğitim kavramı üzerinde durulmuştur. Bu bölüm içerisinde din eğitimi hakkında da bilgi verilmiştir. İkinci bölümde ise ibadet kavramı ele alınmış ve yine bu kavram içerisinde namaz üzerinde araştırma yapılmıştır. Namazın tarihçesi, namaz ile ilgili kavramlar bu bölüm içerisinde yer almıştır. Aynı zamanda ibadetin karakter eğitimi üzerindeki etkileri de bu bölüm içerisinde incelenmiştir.. Üçüncü bölümde namaz eğitimi üzerine Kur’an-ı Kerim’den, kavli ve fiili sünnetten örnekler verilmiş ve bu örnekler üzerinden namaz ibadetinin nasıl öğretileceği üzerinde durulmuştur. Ayrıca temel kaynaklarda İslam alimlerinin namaz eğitimi üzerine açıklamaları da bu bölümde yer almıştır. “Dinin direği”, “göz nuru”, “baş tacı”, “cennet anahtarı” olan namazın doğru şekilde öğretilmesi bunun sonucunda da namaz ibadetinin devamlı olması amacını taşıyan bu çalışmada gayret bizden, tevfik ve hidayet Allah’tandır. 1

Religion, faith, good deeds and services guides human beings by exclusively covering their lives. Worships, the ibadats, regulate the depth of human life. They help a person to become a righteous servant to Allah. Ibadats, as the deeds of an educated servant, function as an integral part of education activity. From the view of Quranic perspective, we see that the ibadats are inseparably together with human interest and desires. Salaat (prayer) keeps one who performs it from falsehood and also rids him from the worldly pressures led by uncontrollable human desires for satisfaction. Fasting (Siyam) is specifically targeted to control physical needs of humans. Zakaat disciplines the acquisitive instinct of people. Hajj guides social interest, confidence building and behavioral tendencies toward aggression. In this paper, we have studied Salaat, which is one of the most important pillars of Islam. Although most of the people already are already aware of the importance, purpose and obligatory nature of salaat, there is sluggishness in performing this daily prayer. As a religious teacher, my approach in this paper has been shaped by the assumption that this behavior is a result of insufficient religious education. In this regard, this study tries to explore how Quran teaches salaat to the people and which words Quran uses to emphasize the salaat. In this study, by examining the honored sayings and acts (sunnahs) of the Prophet (peace upon Him) I also intend to show how the Messenger (peace upon Him) educates his ashab (the companions) regarding performing salaat. Besides this paper also reflects the views and opinions of Islamic scholars about salaat who compiled them in accordance with the principles of Quran and hadiths. The principal aim of this study is to discover the bases of a good education about salaat. Through obtaining good education about salaat, which is one of fundamental pillars of religion, both the continuity of practicing and quality of salaat can been increased. This paper is consisted of four chapters. In the first chapter, general concept of education has been discussed. In this section, general information on religious education has also been given. In the second chapter, the notion of worship (ibadat) has been discussed and salaat has been studied within the framework of this notion. Here, the chronology of salaat and concepts that related to salaat have been studied. In this section, the impacts of salaat over self-education have also dealt with. In the third chapter, the verses of Holy Quran and honored sayings and acts (hadith and sunnah) of the 2 Prophet (peace be upon him) on education of salaat have been exemplified. Through these examples, this chapter tries to explore how education of salaat should be designated. In this section, the views of Islamic scholars on salaat have also been discussed. In the last chapter, the negative behaviors of families and social environment over education process of salaat have been discussed through the examples and some recommendations have been proposed to address and solve this problem The aim of this study is to provide a ground for better education of salaat which is considered as “the pillar of religion” and “the key to heaven’ and in this way to contribute to constitute a continuous practice of salaat.
Keywords: Din Eğitimi; İslam Dini; Namaz